Model of Early Age Santri Attachment to Ustadz at the Maktab Nubdzatul Bayan (Maktubah) Mambaul Ulum Bata-Bata Pamekasan Islamic Boarding School - Mamluatul Hasanah (Al-Fadlan: Journal of Islamic Education and Teaching, 2024)
The number of early age santri who are successful in pursuing religious education such as being able to read yellow books at the age of 7, 8, 9 and 10 years old is inseparable from the success of a teacher in educating students at the Islamic Boarding School so that more and more parents entrust their children to be boarded from an early age. while at the age of not graduating from elementary school is not a time for children to study seriously but a time for children to play and get affection from their parents. From this problem, a model of attachment emerged between early age santri and ustadz. This study aims to determine the attachment model, supporting and inhibiting factors. This study uses a qualitative approach with the type of Case Study. The informants in this study were 10 informants, namely five ustadz and five early-age students. The location of this study was centered at the Nubdzatul Bayan Bata-Bata Islamic Boarding School. The informant determination technique used the purposive method. The data collection method in this study used observation, interviews, and documentation. Data analysis in this study was through data presentation, data reduction and conclusions. The results found in this study were that the attachment model of early-age students at the Nubdzatul Bayan Bata-Bata Islamic Boarding School occurred because of one attachment model, namely the secure attachment model. The existence of the secure attachment model made children feel at home in the boarding school. The supporting and inhibiting factors include supporting factors: First, there is direction from the ustadz to the students so that the students are more persistent in learning. Second, instilling a close relationship between the ustadz and the guardians of the students. Third Instilling togetherness, fourth Instilling exemplary behavior, fifth Maintaining the dignity of students, sixth Giving appreciation, seventh Having a good response to the ustadz with students, eighth Being patient in educating. Inhibiting factors: first Lack of support from family, second Lack of insight, third New students.